Guidelines for Performing Dermatologic Ultrasound Examinations by the DERMUS Group. (17th February 2016) - Wortsman, Ximena; Alfageme, Fernando; Roustan, Gaston; Arias-Santiago, Salvador; Martorell, Antonio; Catalano, Orlando; Scotto di Santolo, Maria; Zarchi, Kian; Bouer, Marcio; Gonzalez, Claudia; Bard, Robert; Mandava, Anitha; et al.
Abstract : Objectives: To support standardization for performing dermatologic ultrasound examinations. Methods: An international working group, called DERMUS (Dermatologic Ultrasound), was formed, composed of physicians who have been working on a regular basis and publishing in peer‐reviewed articles on dermatologic ultrasound. A questionnaire on 5 critical issues about performance of the examinations was prepared and distributed by e‐mail. The areas of discussion included technical aspects, main areas of application, minimum number of examinations per year required for assessing competence, qualifications of the personnel in charge of the examination, and organization of courses. Final recommendations were approved on the basis of the agreement of more than 50% of the members. Results: The minimum frequency recommended for performing dermatologic examinations was 15 MHz. Routine use of color Doppler ultrasound and the performance of spectral curve analysis for assessing the main vascularity of lesions were suggested. Three‐dimensional reconstructions were considered optional. The main dermatologic applications were benign tumors, skin cancer, vascular anomalies, cosmetic field, nail disorders, and inflammatory diseases. The minimum number of examinations per year suggested by the group for assessing competence was 300. A physician and not a sonographer was recommended to be the person in charge of performing the examination. On course organization, a minimum of 2 levels of complexity (basic and advanced) was suggested. Conclusions: There is a need to standardize the performance and quality of dermatologic ultrasound examinations. The present guidelines written by an international group of specialists in the field may support this objective.